Methylation of PLK1 by SET7/9 ensures accurate kinetochore–microtubule dynamics. (21st December 2019) - Yu, Ruoying; Wu, Huihui; Ismail, Hazrat; Du, Shihao; Cao, Jun; Wang, Jianyu; Ward, Tarsha; Yang, Fengrui; Gui, Ping; Ali, Mahboob; Chu, Lingluo; Mo, Fei; et al.
Abstract: Faithful segregation of mitotic chromosomes requires bi-orientation of sister chromatids, which relies on the sensing of correct attachments between spindle microtubules and kinetochores. Although the mechanisms underlying PLK1 activation have been extensively studied, the regulatory mechanisms that couple PLK1 activity to accurate chromosome segregation are not well understood. In particular, PLK1 is implicated in stabilizing kinetochore–microtubule attachments, but how kinetochore PLK1 activity is regulated to avoid hyperstabilized kinetochore–microtubules in mitosis remains elusive. Here, we show that kinetochore PLK1 kinase activity is modulated by SET7/9 via lysine methylation during early mitosis. The SET7/9-elicited dimethylation occurs at the Lys191 of PLK1, which tunes down its activity by limiting ATP utilization. Overexpression of the non-methylatable PLK1 mutant or chemical inhibition of SET7/9 methyltransferase activity resulted in mitotic arrest due to destabilized kinetochore–microtubule attachments. These data suggest that kinetochore PLK1 is essential for stable kinetochore–microtubule attachments and methylation by SET7/9 promotes dynamic kinetochore–microtubule attachments for accurate error correction. Our findings define a novel homeostatic regulation at the kinetochore that integrates protein phosphorylation and methylation with accurate chromosome segregation for maintenance of genomic stability.